Efficacy of generic Artémether -Lumefantrine versus originator Artémether -Lumefantrine in the treatment of uncomplicated malaria in Libreville: randomized, single-blind controlled phase 3 trial - Mfoumou Essono AF; Akendengue B; Tsoumbou Bakana G; Agbanrin AA; Pongui B; Mawili-Mboumba DP; Kouna Ndouongo P; Bouyou Akotet M; Boguikouma JB (Journal of Advances in Internal Medicine, 2024)
BACKGROUND In 2005, artemether -lumefantrine was approved as a first-line drug for the treatment of uncomplicated malaria in Gabon. Due to the high cost of the original drug, the National Health Insurance and Social Guarantee Fund (CNAMGS) promotes the prescription of generic medicines. Sartem - L forte from the GSEZ- Nkok Pharmaceutical Health laboratory is a generic manufactured in Gabon. This prospective equivalence study aimed to determine the effectiveness of Sartem - L forte compared to the innovative product Coartem®. METHODS Participants aged 12 to 59 years with uncomplicated malaria were recruited and randomized to receive Sartem - L forte or Coartem ® as a control. They were expected to return to the study site for follow-up in accordance with World Health Organization recommendations. At each visit, thick and thin blood smears, thick dried blood films, hemoglobin concentrations, and temperature were performed and documented. RESULTS Of 30 participants recruited, 22 met the inclusion criteria. The cure rate was, on day 3, 81.18% for Sartem - L forte and 100% for Coartem® and no early treatment failure was observed in both treatment arms. Both drugs showed good early clearance of parasites, with no participant experiencing significant peripheral parasitemia on day 3. Fever reduction was also excellent in both arms. No participant had a temperature >37.5°C on day 3. CONCLUSION The results of this study indicate that Sartem - L forte and Coartem® are equivalent and effective in the management of uncomplicated malaria in adolescents and adults in Gabon.